2D–2D heterostructure g-C3N4-based materials for photocatalytic H2 evolution: Progress and perspectives - Mehmood, Rashid; Ahmad, Zia; Hussain, Muhammad Bilal; Athar, Muhammad; Akbar, Ghulam; Ajmal, Zeeshan; Iqbal, Sikandar; Razaq, Rameez; Ali, Mohammad Arif; Qayum, Abdul; Chishti, Aadil Nabi; Zaman, Fakhr uz; et al. (Frontiers in Chemistry, 2022)
Photocatalytic hydrogen generation from direct water splitting is recognized as a progressive and renewable energy producer. The secret to understanding this phenomenon is discovering an efficient photocatalyst that preferably uses sunlight energy. Two-dimensional (2D) graphitic carbon nitride (g-C3N4)-based materials are promising for photocatalytic water splitting due to special characteristics such as appropriate band gap, visible light active, ultra-high specific surface area, and abundantly exposed active sites. However, the inadequate photocatalytic activity of pure 2D layered g-C3N4-based materials is a massive challenge due to the quick recombination between photogenerated holes and electrons. Creating 2D heterogeneous photocatalysts is a cost-effective strategy for clean and renewable hydrogen production on a larger scale. The 2D g-C3N4-based heterostructure with the combined merits of each 2D component, which facilitate the rapid charge separation through the heterojunction effect on photocatalyst, has been evidenced to be very effective in enhancing the photocatalytic performance. To further improve the photocatalytic efficiency, the development of novel 2D g-C3N4-based heterostructure photocatalysts is critical. This mini-review covers the fundamental concepts, recent advancements, and applications in photocatalytic hydrogen production. Furthermore, the challenges and perspectives on 2D g-C3N4-based heterostructure photocatalysts demonstrate the future direction toward sustainability.